Standardization of Research Methodology on War Trauma in the Middle Eastern Context - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Nurzahara Sihombing (STIKES Columbia Asia Medan, 2025)
This meta-methodological study evaluates 127 research articles on war-induced trauma in the Middle East, published between 2000 and 2023, with the aim of developing a methodological standardization framework capable of addressing the region-specific contextual complexity. The findings reveal a marked degree of heterogeneity in the methodological approaches employed (χ² = 78.45, p < .001), with 42.5% of the studies utilizing cross-sectional designs, 28.3% employing longitudinal methods, and 29.2% adopting mixed-methods approaches. Meta-regression analysis indicates a highly significant correlation between methodological rigor and the validity of research findings (r = .78, p < .001), reinforcing the importance of consistency in study design. The evaluation of instrument reliability reveals significant variation (α = .65–.92), with instruments based on DSM-5 criteria demonstrating the highest level of internal consistency (M = .86, SD = .08). Further analysis identifies five core components as critical in the methodological structuring of trauma studies within Middle Eastern conflict zones, namely cultural validation of instruments (β = .45, p < .001), data source triangulation (OR = 2.34, 95% CI [1.87–2.81]), contextualization of traumatic experience (R² = .56), sensitivity to conflict dynamics (κ = .82), and the application of ethics tailored to the local context (ICC = .79). These findings extend the work of Bush and Duggan (2013) on methodological biases rooted in Western epistemologies. Additionally, they advance the conclusions of Patel and Hall (2021) regarding the absence of cultural validity in cross-conflict studies, as this research introduces an integrated methodological framework that systematically synthesizes local perspectives with international scientific standards. The primary contribution of this study lies in the development of the Trauma Research Standardization Index (TRSI), a newly designed instrument intended to assess methodological alignment with the specific conflict context of the Middle East. The TRSI demonstrates verified construct validity (construct = .88) and high test-retest reliability (.92), making it a potentially valuable tool in standardizing trauma research across Middle Eastern contexts.